Klasifikasi Kriteria Kemampuan Siswa Untuk Heterogenitas Kelompok Belajar Menggunakan Agglomerative Hierarchical Cluster Analysis - Suryaningtyas, Wahyuni; Kristanti, Febriana (Universitas PGRI Madiun, 2023)
Research on the classification of students' ability criteria uses quantitative data. In this research, the data used was secondary data in the form of PTS Mathematics data for class VII-B SMP Muhammadiyah 10 Surabaya. Determination of classification using the Sturges' Rule method, hypothetical categorization, and agglomerative hierarchical cluster analysis. The results of the classification research obtained for each method provide different intervals to determine student ability criteria. In Sturges' Rule and agglomerative hierarchical cluster analysis, although there are differences in the resulting intervals, the number of student frequencies is almost the same for each student's ability criteria. Meanwhile, the intervals on the hypothetical categorical method give different results with different frequencies for the number of frequencies on each criterion when compared to the Sturges' Rule method and agglomerative hierarchical cluster analysis. Measuring the accuracy of classification based on the difference in the mean, median, and standard deviation values, the comparison of the accuracy of the frequency distribution table with the cluster method is more accurate than the Sturges method and hypothetical categorization. The interval resulting from the cluster analysis gave results close to the mean, median, and standard deviation of PTS grade VII-B data at SMP Muhammadiyah 10 Surabaya.